Resting and exercise-induced IL-6 levels in children with Type 1 diabetes reflect hyperglycemic profiles during the previous 3 days - Rosa, Jaime S. (American Physiological Society, 2010)
Poor glycemic control in Type 1 diabetes (T1DM) causes long-term cardiovascular complications, at least in part via chronic, low-grade inflammation associated with recurrent hyperglycemia. While physical activity can reduce both inflammation and cardiovascular risks, the underlying molecular mechanisms remain unclear. This is particularly important for T1DM children, for whom the prevention of long-term cardiovascular complications must include optimization of exercise-related anti-inflammatory strategies. We therefore studied the effect of prior hyperglycemia on resting and exercise-induced inflammatory status (plasma IL-6) in T1DM children. Glycemia was continuously recorded with a continuous glucose monitoring system (CGMS) system for 63 h preceding a 30-min intermittent cycling exercise protocol at ∼80% peak rate of oxygen uptake (V̇o(2max)). Euglycemia (4.4–6.1 mM) was maintained for 90 min before, during, and 30 min after exercise. IL-6 plasma concentration (pg/ml) was measured at baseline, at end exercise, and 30 min postexercise. Subjects were then divided into quartiles based on average glycemia during the CGMS recording. IL-6 levels (pg/ml) were lowest in the quartile with lowest average 3-day glycemia and increased proportionally to greater hyperglycemic exposure; this was observed at baseline (0.86 ± 0.10, 1.06 ± 0.16, 1.14 ± 0.14, 1.20 ± 0.16), absolute IL-6 change (Δ) at end exercise (0.20 ± 0.16, 0.32 ± 0.10, 0.48 ± 0.09, 0.62 ± 0.13), and Δ at 30 min postexercise (0.49 ± 0.13, 0.71 ± 0.16, 0.89 ± 0.14, 1.38 ± 0.33). Therefore, poorly controlled glycemic profile, even in the 63 h preceding an exercise challenge, can alter inflammatory adaptation in T1DM children. Our data underscore the necessity to fully understand all molecular aspects of physical activity to provide the scientific rationale for exercise regimens that will be able to maximize health benefits for T1DM children.